Does the habitual mastication side impact jaw muscle activity? - Turcio, Karina Helga Leal [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Guiotti, Aimée Maria [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP]; Brandini, Daniela Atili [UNESP] (Elsevier, 2016)
Objective To compare electrical activity in the anterior temporal and masseter muscles on the habitual (HMS) and non-habitual mastication side (NHMS), during mastication and in the mandibular postural position. In addition, the increase in electrical activity during mastication was assessed for the HMS and NHMS, analysing both working (WSM) and non-working side during mastication (NWSM). Methods A total of 28 healthy women (18-32 years) participated in the study. They were submitted to Kazazoglu's test to identify the HMS. Bioresearch 'Bio EMG' software and bipolar surface electrodes were used in the exams. The exams were conducted in the postural position and during the unilateral mastication of raisins, on both the HMS and NHMS. The working and non-working side on HMS and NHMS were assessed separately. The obtained data were then statistically analysed with SPSS 20.0, using the Paired Samples Test at a significance level of 95%. Results The differences in the average EMG values between HMS and NHMS were not statistically significant in the postural position (Temporal p = 0.2; Masseter p = 0.4) or during mastication (Temporal WSM p = 0.8; Temporal NWSM p = 0.8; Masseter WSM p = 0.6; Masseter NWSM p = 0.2). Differences in the increase in electrical activity between the masseter and temporal muscles occurred on the working side, on the HMS and NHMS (p = 0.0), but not on the non-working side: HMS (p = 0.9) and NHMS (p = 0.3). The increase in electrical activity was about 35% higher in the masseter than in the temporal muscle. Conclusions Mastication side preference does not significantly impact electrical activity of the anterior temporal and masseter muscles during mastication or in postural position.
Keywords: Electromyography; Jaw muscle; Mastication side